Haemodynamic and electrocardiographic consequences of severe nicorandil toxicity. Issue 1 (1st January 2003) - Greenwood, J P; Malik, I; Jennings, P; Stevenson, R N
Abstract : A 35 year old woman was admitted to the emergency department two hours after ingesting 60×20 mg tablets of nicorandil, total 1.2 g. The dominant feature of icorandil toxicity was profound peripheral vasodilatation associated with coronary hypoperfusion. Despite widespread electrocardiographic signs of myocardial ischaemia, there was no evidence of myocardial damage and no serious cardiac arrhythmia. Volume loading and pressor support proved to be an effective treatment strategy.